INSECURITY CHALLENGES, BANE TO NATIONAL DEVELOPMENT: THE NIGERIA EXPERIENCE. - Okolo, Ekenedilichukwu A.; Abalogu, Divine Maduk (Igwebuike Journal: An African Journal of Arts & Humanities, 2024)
Presently, the Nigeria society is suffocating from series of societal challenges of which insecurity is obviously inclusive and occupies a prime spot in the nation's structural process. The heightened rate of insecurity challenges in the history of the country is considerably alarming, with myriad effects visible in all ramifications and dimensions of the society. The Nigeria nation is grappling with the endemic realities of underdevelopment which is intricately linked to the issues of insecurity in the country. Urban and infrastructural development is among the Sustainable Development Goals (SDGs) adopted by the United Nations Member States with an actualization target in the year 2030. Despite the concerted effort in achieving this goal, insecurity has continued to pose a big threat by frustrating all the available avenues employed for the development of the country. Developmental blueprint employed by the government seems to be unattainable due to the indices of insecurity challenges evident in terrorism, kidnapping, arm robbery, banditry, vandalization and massive destruction of lives and properties which have subjected the populace to live in abject fear, tension and apprehension. Against this backdrop, it will be worthwhile to posit that for development to be achieved in Nigeria, the trend of insecurity must be arrested. This study adopts the sociological method of research and will be framed with Structural functionalism theory. The paper therefore observes that insecurity challenges are rife in Nigeria which is the rationales for underdevelopment of the country. It further observes that the reason behind insecurity challenges is based on poverty, unemployment, agitations and unsatisfactory ends among the ethnicities in Nigeria. It finally observes that if the challenges of insecurity are tackled, the development of the country will take an unprecedented acceleration. The paper concludes that Nigeria government should be alive and active in her war against insecurity in Nigeria which will give way to national development. The study therefore recommends that the government and all well-meaning Nigerians should take the insecurity situation of the country seriously. Also, the government should create a forum for dialogue among the aggrieved ethnic groups for the resolution of protest and agitations. Finally, Nigerians should endeavor to build legacies of peace for an environment devoid of hostility, tension, apprehension and fear towards achieving the sustainable development goals.